Role of Prefrontal Cortex on Recognition Memory Deficits in Rats following 6-OHDA-Induced Locus Coeruleus Lesion. (11th July 2020) - Sampaio, Tuane Bazanella; Marques, Naiani Ferreira; Binder, Luisa Bandeira; Tasca, Carla Inês; Prediger, Rui Daniel
Abstract : Degeneration of the locus coeruleus (LC), the main source of cerebral noradrenaline (NA), has been reported in diverse neurodegenerative diseases, including Parkinson's diseases (PD). There is increasing evidence indicating the role of NA deficiency in the prefrontal cortex (PFC) and the development of early cognitive impairments in PD. Here, we evaluated whether a selective noradrenergic lesion of LC caused by 6-hydroxydopamine (6-OHDA) may induce memory deficits and neurochemical alterations in the PFC. Adult male Wistar rats received stereotaxic bilateral injections of 6-OHDA (5  μ g/2  μ l) into the LC, and two stainless-steel guide cannulas were implanted in the PFC. The SHAM group received just vehicle. To induce a selective noradrenergic lesion, animals received nomifensine (10 mg/kg), a dopamine transporter blocker, one hour before surgery. 6-OHDA-lesioned rats displayed impairments of the short- and long-term object recognition memory associated to reduced content of tyrosine hydroxylase in the LC. Neurochemical analysis revealed an altered mitochondrial membrane potential in LC. Regarding the PFC, an increased ROS production, cell membrane damage, and mitochondrial membrane potential disruption were observed. Remarkably, bilateral NA (1  μ g/0.2  μ l) infusion into the PFC restored the recognition memory deficits in LC-lesioned rats. These findings indicate that a selective noradrenergic LC lesion induced by 6-OHDA deregulates a noradrenergic network in the PFC, which could be involved in the early memory impairments observed in nondemented PD patients.